Perbaikan desain tungku hemat energi untuk produsen keumamah di Kota Banda Aceh (Design improvement of energy-efficient stove for keumamah producers in Banda Aceh) - Hasan, Hafidh; Anwar, Sri Haryani; Rohaya, Syarifah (Buletin Pengabdian, 2021)
This community service (PKM) aims at identifying problems and providing solutions for keumamah producers, particularly at the stage of fish boiling prior to the drying of keumamah. PKM partners have been using open stoves with incomplete combustion, thus requiring a lot of wooden biomass. Combustion with this open furnace produces a lot of smoke, soot and pollutant gases. As the results, the purchase of firewood is the biggest material spending after fish and has an impact on reducing the profit margins of producers. Furthermore, pollutant gases and smoke and combustion particles have a negative impact on the health of employers, workers, quality and comfort as well as the environment around and in the production site. The solution given to the two partners is the specially designed and manufactured energy-efficient stoves that include appropriate feature to reduce wooden biomass consumption by up to 33% and minimize smoke and pollutant gases. The use of energy-efficient stoves can reduce expenses on wood biomass, improve comfort and peace of the environment around the business location and improve the welfare of the producers. In addition, the quality of the public life, competitiveness and expansion of employment opportunities for the surrounding community also increase and provide a multiplying effect for economic growth around the business location.